HUBUNGAN STATUS NUTRISI BERDASARKAN SUBJECTIVE GLOBAL ASSESSMENT (SGA) DAN PATIENT GENERATED SUBJECTIVE GLOBAL ASSESSMENT (PG-SGA) TERHADAP KONTROL GULA DARAH PADA PASIEN DIABETIK NEFROPATI - Krisnanda, Made Yogi; Saraswati, Made Ratna (E-Jurnal Medika Udayana, 2017)
Nutritional status is one of the parameters in the control of diabetes disease. Nutritional status can be measured with anthropometry, SGA, PG-SGA etc. But PG-SGA SGA and its still subjective, so it is necessary to use other parameters as reference in disease control type 2 diabetes. The purpose of this study was to identify the nutritional status using the method (SGA and PG-SGA) and their effects on blood sugar control in patients with type 2 diabetes mellitus with complications of nephropathy in Sanglah. This type of research is observational analytic cross-sectional design. Total sample of this study is 50 people, who were taken consecutively at Outpatient Polyclinic and Inpatient in Internist Department General Hospital Sanglah - Denpasar. Univariate and bivariate variables were analyzed using SPSS, with significance ? = 0:05. The results showed that of the chi-square statistical test, there was no significant association between SGA nutritional status (p = 0.923) and PG-SGA (p = 0.566) to control blood sugar in diabetic nephropathy patients in Sanglah. Then, PG-SGA has a sensitivity 66.6% and specificity of 43% .in detect nutritional status by SGA in patients with type II diabetes mellitus with complications of diabetic nephropathy in Sanglah. From the results of this study concluded there was no relationship nutritional status based on SGA and PG-SGA with blood sugar control in patients with diabetic nephropathy in Sanglah. Sensitivity and specificity of the PG-SGA SGA low based on nutritional status in patients with diabetic nephropathy.   Keywords: Nutritional status, PG-SGA and SGA, control blood sugar, Diabetic Nephropathy